Turning organic waste into organic fertilizers in the village Namo Bintang Deli Serdang regency - Budi Mulya, Miswar; Alexander Barus, Ternala; H.J, Arlen; Nursal; Nurtjahya, Kiki (Talenta Publisher, 2019)
Community service activities titled Transforming Organic Waste into Organic Fertilizer in Namo Bintang Village in May - November 2019. This activity aims to convert organic waste into organic fertilizer that has economic value, and does not endanger the environment. The method used is counseling, lectures and training as well as monitoring and evaluation with the community directly to the field. Organic waste processing is carried out in several places in the village of Namo Bintang with the approval of the village head and the community. The activities are carried out by means of counseling and lectures, explanations of theories and integrated waste management techniques that are followed by the farmers and scavenger groups of Namo Bintang Village. The community listens to the material delivered by the community service team. The training was conducted by community groups of farmers and scavengers in Namo Bintang Village. Peasant and scavenger community groups are trained by the community service team. All carried out this activity by proactively conducting training to get results in the form of fertilizer from organic waste. The results were reviewed by community groups after 10 days of training to see organic fertilizer. The equipment for utilizing organic waste is also very simple so that community groups can make it themselves. And finally the monitoring and evaluation of the success of monitoring the work in the field will be carried out by going directly to the field together, monitoring by visiting to find out whether the community can do it themselves, besides that the relationship will be carried out by telephone to overcome the problems that arise. In general, community service activities have been successfully carried out and seen a good cooperative relationship between the Higher Education, especially the Implementation Team, government officials and the community in Namo Bintang Village. The village community realizes the importance of saving the environment from increasing their life expectancy because they can make their own fertilizer / compost.